Hazard Risk Analysis and Cathodic Maintenance Timing With Total Producvtive Maintenance Approach: Analisis Risiko Bahaya dan Penentuan Waktu Perawatan Katodik Dengan Pendekatan Total Producvtive Maintenance - Dzulfikar, Tegar; Widiasih, Wiwin (Universitas Muhammadiyah Sidoarjo, 2024)
XYZ is a major player in natural gas distribution in Indonesia, with an extensive pipeline connecting production sources with a wide range of consumers, including households, industries, and power plants. The network ensures an efficient and safe gas supply throughout the region, with good distribution control for reliable service. However, corrosion problems in pipes can threaten the integrity of the system. To overcome this, PT. XYZ implements precautions such as protective coating and cathodic protection. Risk analysis and scheduled maintenance help reduce the impact of corrosion and minimize maintenance costs. The findings of this study reveal that optimal treatment can be established by analyzing potential risks through certain methods. The approach allows for the identification of possible hazards and helps in determining the most effective treatment measures.Thus, organizations can take appropriate precautions to reduce risks and ensure efficient maintenance. Total Productive Maintenance TPM, which recommends that maintenance be carried out every 3 days, has succeeded in reducing the maintenance cost of PT. XYZ Previously, the company incurred maintenance costs from Rp. 60,600,000 to Rp. 55,200,000 per month with an efficiency of 9.78% through the analysis of the maintenance budget. With the right precautions, PT. XYZ ensures efficient maintenance to maintain the smooth distribution of natural gas in a sustainable manner.